STUDY OF THE USE OF CHAT GPT TO COMPLETE STUDENTS’ ACADEMIC ASSIGNMENTS - Soffi Asri; Joko Santoso (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This research investigates how students at the Faculty of Social and Political Sciences, Jenderal Soedirman University, utilize Chat GPT to complete academic tasks and how this affects academic ethics. It is driven by the rising use of artificial intelligence—particularly Chat GPT—which is reshaping students’ learning patterns and assignment completion strategies. Employing a descriptive qualitative approach, data were gathered through in-depth interviews, observations, and documentation. The findings suggest that a desire for time efficiency, limited access to academic supervisors, and academic pressure drive the use of ChatGPT. Students use Chat GPT to generate ideas, draft task structures, and develop thesis outlines. However, most students still revise the output to avoid plagiarism. The study reveals that uncritical use of ChatGPT can lead to academic ethical violations. Based on Robert K. Merton’s theory of anomie, such deviations arise from systemic pressures that emphasize academic success while overlooking individual capacities and talents. Thus, there is an urgent need for clear academic ethical guidelines in the use of artificial intelligence within higher education. This study extends Merton’s anomie theory by demonstrating how students adapt innovatively—utilizing artificial intelligence, such as ChatGPT—when academic goals conflict with limited resources. Universities should establish clear guidelines for ethics and digital literacy to ensure the responsible use of artificial intelligence in learning.